A black phosphorus/manganese dioxide nanoplatform: Oxygen self-supply monitoring, photodynamic therapy enhancement and feedback. (February 2019) - Liu, Jintong; Du, Ping; Liu, Tianrui; Córdova Wong, Bernardino J.; Wang, Weiping; Ju, Huangxian; Lei, Jianping
Abstract: Selecting the timing of laser treatment is an important task for improving O2 -dependent photodynamic therapy (PDT) efficiency. Here, a black phosphorus-based strategy was developed for dual-mode monitoring oxygen self-supply, enhancing photodynamic therapy, and feeding back therapeutic effect. The hybridized nanoplatform (R-MnO2 -FBP) was prepared by assembly of Rhodamine B (RhB)-encapsulated manganese dioxide (R-MnO2 ) as O2 supplier and indicator, and fluorescein isothiocyanate (FITC)-labelled peptide-functionalized black phosphorus as the theranostic agent. The time-dependent assays suggested that the O2 release was proportional to the liberation of Mn 2+ and RhB in the R-MnO2 -FBP system. After specific delivery into cancer cells, R-MnO2 -FBP was dissociated in the acidic and H2 O2 -rich environment and generated oxygen to overcome hypoxia-associated PDT resistance. In the meantime, it released both Mn 2+ and RhB dye, leading to dual-mode (magnetic resonance imaging/fluorescence imaging) monitoring of the oxygen self-supply process. More significantly, the imaging-guided PDT in hypoxic cells displayed 51.6% of cell apoptosis at optimizing timing of laser application, which could also be confirmed by the FITC fluorescence recovery induced by the activated caspase-3 in apoptotic cells. In vivo photonic therapy by R-MnO2 -FBP further demonstrated the ability of R-MnO2 -FBP to choose the timing of laser application, providing an efficient approach for the enhancement of PDT process. Graphical abstract: A multifunctional black phosphorus was designed as all-in-one theranostic nanoplatform for cancer-cell target delivery, dual-modal tracking of the pH/H2 O2 responsive oxygen supply, photodynamic therapy enhancement, and feeding back therapeutic efficacy in real time. Image 1 Highlights: Black phosphorus-based theranostic system is developed for enhanced PDT. Dual-modal tracking of oxygen supply guides the timing of laser application. A self-feedback system is established for the therapeutic response in real time. All-in-one theranostic platform is achieved with whole-process self-tracking.